Comparative study on torque characteristics of permanent magnet synchronous reluctance motors with different axial hybrid rotors. (August 2022) - Fan, Zheming; Liu, Guangwei; Jin, Shi; Song, Zhihuan; Wang, Jianqiao
Abstract: An axial hybrid permanent magnet synchronous reluctance machine (AHPM-SynRM) is proposed in this paper. The structure is a combination of synchronous reluctance rotor and two permanent magnet rotors. The proposed design includes three axially parallel rotors, the reluctance axis coincides in phase with the permanent magnet axis by rotating the synchronous reluctance machine (SynRM) rotor, which could increase the average torque. In the condition of the volume of permanent magnets stays unchanged, the relationship between the axial length ratio of different rotor parts and the maximum torque is also analyzed. Moreover, air gap magnetic isolation is designed between each rotor part, so there is no serious magnetic field coupling between different rotors and each rotor part could be separately designed. The analysis results prove the proposed machine has significantly higher torque performance than the permanent magnet assisted machine. (PM-SynRM).